Pengembangan Aplikasi Kasir Cuci Steam Berbasis Desktop Menggunakan Model Waterfall - Aries Saifudin; Irpan Kusyadi; Ari Asyari; Iwan Setiawan; Kiki Mahendra; Muhamad Rafli Mauludin (Jurnal Informatika Universitas Pamulang, 2022)
Motorcycle and car washing business is a service business that cleans car or motorcycle vehicles. This job is very helpful for those who don't have time to clean their vehicle. However, many motorcycle and car wash businesses still use manual payments, such as when the customer wants to pay but records the payment manually in the book and there is no proof of the transaction receipt, and when the Steam owner wants to pay a financial income statement, the cashier must check it by opening the income book. last month, last week or yesterday, and the cashier inevitably has to count the number of customers and the amount of revenue every day, week or even month, according to the requirements of the steam boss. In addition, many things often arise when report cards are lost, forgotten or burned. This is very risky when calculating gross income due to human error. For this reason, the author wants to solve the problems that often occur by making a cash register program to sell motorcycles and cars. This motorbike and steam car payment application was created using the Java NetBeans application and MySQL database. Therefore, the hope is that it can help business owners and cashiers improve motorbike and car washing payment services, and the data is directly stored in the database, so the owner or cashier does not need to save and record in a book.